2020
DOI: 10.1186/s12893-020-00993-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metallic stenting as a bridge to elective surgery versus emergency surgery for acute malignant right-sided colorectal obstruction

Abstract: Background The use of a self-expandable metallic stent (SEMS) as a bridge to surgery has increased for patients with obstructing colorectal cancer. However, relatively few reports have compared SEMS as a bridge to elective surgery for acute malignant obstruction of the right-sided colon (MORC) vs. emergency surgery (ES). This study aimed to evaluate the benefits of elective surgery after SEMS placement vs. ES for patients (including stage IV cases) with acute MORC. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Second, certain parameters that evaluate SEMS placement difficulties, such as procedure time, were not compared. Third, this study might have yielded higher complications rates in the right-sided group than in previous studies [15,17]. However, some studies have reported similar complication rates [26,33]; therefore, controversy remains.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Second, certain parameters that evaluate SEMS placement difficulties, such as procedure time, were not compared. Third, this study might have yielded higher complications rates in the right-sided group than in previous studies [15,17]. However, some studies have reported similar complication rates [26,33]; therefore, controversy remains.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, differences in the success rates of SEMS placement between right-and left-sided OCRCs remain controversial [11][12][13]. Moreover, although a previous systematic review and some retrospective studies have demonstrated satisfactory postoperative outcomes of SEMS use for right-sided OCRC as a BTS compared with emergency surgery [14][15][16], few studies have compared the postoperative short-term outcomes of SEMS use as a BTS between right-and left-sided OCRCs.…”
Section: Level Of Oral Intake Scorementioning
confidence: 99%
“…In recent years, self-expandable metal stents (SEMS) have been used more and more as a bridge to surgery for patients with obstructive colorectal cancer; they offer significant advantages, and they offer efficacy and safety comparable to HP in the management of malignant rectosigmoid obstruction, especially in people with high ASA risk, or in an advanced tumor stage, with faster recovery and shorter hospitalization time [38][39][40]. The use of SEMSs in the presence of perforation or peritonitis is contraindicated; in these conditions, a Hartmann resection is preferred [41].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 8–13% of patients with advanced colon cancer present with an obstruction of the large bowel, and the left side colon is the most common site of obstruction [ 1 ]. Acute colorectal obstruction is a medical emergency that necessitates immediate management.…”
Section: Introductionmentioning
confidence: 99%